2017
DOI: 10.1039/c6md00496b
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, solubilization, cytotoxicity and antioxidant activity of aminomethylated dihydroquercetin

Abstract: A dihydroquercetin derivative (DHQA) was prepared through aminomethylation to overcome the low water solubility and bioavailability of dihydroquercetin (DHQ). DHQA was characterized through HPLC, nuclear magnetic resonance, scanning electron microscopy, X-ray diffraction, and thermogravimetric analyses. DHQA was converted into the amorphous form, but the major structure of DHQ remained unchanged. Solubilization and dissolution tests were also performed. Results showed that the solubility and dissolution rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Industrially isolated taxifolin is very slightly soluble in water at room temperature; it therefore has limited bioavailability (Yang et al, 2016). There are many ways to increase its bioavailability, such as micronization (Zu et al, 2012), chemical modification (Li et al, 2017) and nanodispersion preparation (Shikov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Industrially isolated taxifolin is very slightly soluble in water at room temperature; it therefore has limited bioavailability (Yang et al, 2016). There are many ways to increase its bioavailability, such as micronization (Zu et al, 2012), chemical modification (Li et al, 2017) and nanodispersion preparation (Shikov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The known compounds ( Figure 1) were identified as isoswertisin ( 4 ), [14] taxifolin ( 5 ), [15] caudatan B ( 6 ), [16] (2 R ,4 R )‐2‐(5‐hydroxy‐2‐methylphenyl)‐8‐(3‐methylbut‐2‐en‐1‐yl)‐4‐(l‐oxidaneyl)chromane‐3,7‐diol ( 7 ), [17] 8‐prenykaempferol ( 8 ), [18] 2‐(2,4‐dihydroxyphenyl)‐3,5‐dihydroxy‐7‐methoxy‐8‐(3‐methylbut‐2‐en‐1‐yl)chroman‐4‐one ( 9 ), [19] 8‐prenylquercretin ( 10 ), [20] citrusinol ( 11 ), [21] pulcheloid B ( 12 ), [22] yokovanol ( 13 ), [23] apigenin ( 14 ), [24] 8‐dimethylallyltaxifolin ( 15 ), [25] genistein ( 16 ), [26] naringenin ( 17 ), [27] shuterin ( 18 ), [28] kaempferol ( 19 ), [29] aromadendrin ( 20 ), [30] luteolin ( 21 ), [31] quercetin ( 22 ) [29] by comparing their spectrascopic data with those from previous reports.…”
Section: Resultsmentioning
confidence: 99%
“…Behavior of luteolin, quercetin, rutin, hesperetin and diosmetin in the Mannich reaction in terms of reactivity and preferred reaction site was examined, and evaluation of the cytotoxic activity of the resulting aminomethylated flavonoids against MDA‐MB‐231 cells showed that bis‐Mannich bases derived from rutin and hesperetin, (but not from quercetin) inhibited the growth of cancer cells at 100 μM to a greater extent than the parent flavonoids, and that compound 40 (Figure 4) was the most potent in this series with IC 50 =7.6 μM [53] . Derivatization of dihydroquercetin by aminomethylation with ʟ‐proline as amine reagent led to Mannich base 41 (Figure 5) with moderate activity (50 % effective concentration EC 50 =138 μM) against HeLa cells [54] . Aminomethylation of dihydroquercetin with secondary cyclic amine N ‐oxides, whose use as amine reagents in the Mannich reaction was primarily intended to improve the substrate's antioxidant activity, afforded compounds 42 (Figure 5) with claimed selective cytotoxicity against various tumor cells, although no actual data has been made available [55] .…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Derived F...mentioning
confidence: 95%
“…[53] Derivatization of dihydroquercetin by aminomethylation with �-proline as amine reagent led to Mannich base 41 (Figure 5) with moderate activity (50 % effective concentration EC 50 = 138 μM) against HeLa cells. [54] Aminomethylation of dihydroquercetin with secondary cyclic amine N-oxides, whose use as amine reagents in the Mannich reaction was primarily intended to improve the substrate's antioxidant activity, afforded compounds 42 (Figure 5) with claimed selective cytotoxicity against various tumor cells, although no actual data has been made available. [55] Other examples of Mannich bases of flavonoids with antiproliferative activity include aminomethyl derivatives of thioxoflavones 43 (several compounds had IC 50 values around 10 μM against HeLa and HCC1954 cells and IC 50 values around 20 μM against SK-OV-3 cells), [56] aminomethylated naringenins 44 (lack of cytotoxicity), [57] and Mannich bases 45 of bergenin with a 1,2,3-triazole appendage (compound 45 (R = 3,5-(CF 3 ) 2 ) was the most potent in the series with IC 50 values of 1.86 μM and 1.33 μM against A-549 and HeLa cells, respectively) [58] (Figure 5).…”
Section: Anticancer and Cytotoxic Activity Of Mannich Bases Derived F...mentioning
confidence: 99%